LEVEL LITERASI MATEMATIKA SISWA DALAM MENYELESAIKAN SOAL PISA KONTEN CHANGE AND RELATIONSHIP BERDASARKAN GAYA KOGNITIF - Pratiwi, Devi Anggraeni; Trapsilasiwi, Dinawati; Oktavianingtyas, Ervin; Sunardi, Sunardi; Murtikusuma, Randi Pratama (Kadikma, 2019)
This study aims to describe the mathematical literacy of field-dependent (FD) students and field-independent students (FI) in solving PISA questions on Change and Relationship content in terms of the achievement of mathematical literacy levels. The PISA issue of Change and Relationship content is related to curriculum material, namely functions and algebra. This research is a qualitative descriptive study. The subjects in this study were students of class X MIPA 6 of SMA Negeri 1 Jember with 29 students consisting of 6 field-dependent (FD) students and 23 field-independent (FI) students. The results showed that the level of mathematics dependent literacy of field-dependent students was at level 2 (66.67% or as many as 4 students) and level 5 (33.33% or as many as 2 students) and the level of mathematics literacy of independent field students was at level 2 (13 % or as many as 3 students), level 5 (69.56% or as many as 16 students) and level 6 (17.4% or as many as 4 students).